1995
DOI: 10.1099/00207713-45-1-104
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Mycoplasma Strain ISM1499 and Its Assignment to the Acholeplasma oculi Strain Cluster

Abstract: A mycoplasma strain designated ISM1499 was used to develop a mycoplasma genetic system (G. G. Mahairas and F. C. Minion, J. Bacteriol. 171:1775-1780,1989; G. G. Mahairas, C. Jian, and F. C. Minion, Gene 93:61-65, 1990), but phenotypic inconsistencies led to the conclusion that this organism had been classified incorrectly as a member of the species Mycoplasma pulmonis. Studies were initiated to determine the proper taxonomic position of ISM1499, and on the basis of the results of our genetic analysis, this str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Furthermore, to select the supposedly rare events of integration, we are currently trying to counter-select the replication of the oriC plasmid, as proposed for other bacteria (36). Although a case of homologous recombination with M. pulmonis using suicide vectors has been reported (28), further studies indicated that these results were obtained with a strain that did not belong to the species M. pulmonis but belonged to the other mollicute species Acholeplasma oculi (1,9,28). Our results confirmed that homologous recombination for M. pulmonis using suicide vectors is difficult, if not impossible, to detect.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, to select the supposedly rare events of integration, we are currently trying to counter-select the replication of the oriC plasmid, as proposed for other bacteria (36). Although a case of homologous recombination with M. pulmonis using suicide vectors has been reported (28), further studies indicated that these results were obtained with a strain that did not belong to the species M. pulmonis but belonged to the other mollicute species Acholeplasma oculi (1,9,28). Our results confirmed that homologous recombination for M. pulmonis using suicide vectors is difficult, if not impossible, to detect.…”
Section: Discussionsupporting
confidence: 76%
“…Until now, the phylogenetic analysis of mycoplasmas and ureaplasmas has been based on approximately 1,000 bp of 16S rRNA gene (2,3,21). The phylogenetic analysis based on these sequences enables the prototype strains to be classified into species; however, this size, approximately 1,000 bp of a nucleotide sequence, is too long for the phylogeny-based rapid identification of PCR products to be applied with clinical materials.…”
Section: Discussionmentioning
confidence: 99%
“…However, using several species-specific PCRs to determine all human mycoplasmas and ureaplasmas associated with urethritis would be a complicated undertaking. To date, amplification of the genome by PCR, followed by determination of the nucleotide sequences and phylogenetic analysis has become a generalized technique for both the classification and identification of etiological agents (2,3,12,21,28). When the nucleotide sequences of 16S rRNA genes were compared by van Kuppeveld et al (33), the 5Ј flanking region of the variable V3 region and 3Ј flanking region of the variable V6 region were well conserved among the 15 prototype strains of mycoplasmas and ureaplasmas.…”
mentioning
confidence: 99%
“…Strain 232 of M. hyopneumoniae was isolated from a pig infected with strain 11 (4,30) and has been commonly used to study virulence and vaccination regimens in the United States (49,54,55). Chromosomal DNA was isolated by the method of Artiushin et al (1), and two libraries were constructed. Chromosomal DNA was incompletely digested with Tsp509I and size fractionated on sucrose gradients, and 2-to 4-kb fragments were ligated into EcoRI-digested, dephosphorylated pZERO vector (Invitrogen) with selection for kanamycin resistance (library 1).…”
Section: Methodsmentioning
confidence: 99%